Impact of Conversion in Law Number 5 Years 1960 Concerning Basic Rules on Agrarian Costs on the Rights of Indigenous People's Ownership in Bali - I Dewa Gede Arie Kusumaningrat (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2019)
Agrarian development in Indonesia has experienced a long history, it is noted that the milestone in the development of agrarian law in Indonesia dates back to the Dutch colonial period in Indonesia. During the Dutch colonial period in Indonesia there was a dualism of agrarian arrangements in Indonesia, besides that the regulations made by the colonial government did not provide welfare for the people of Indonesia because it was far from a sense of justice. After Indonesia's independence in 1945, agrarian became one of the important concerns of the government and in the end after going through a long process Indonesia established the Basic Agrarian Law (UUPA. With the creation of UUPA providing fundamental changes to the agrarian in Indonesia, especially in the land sector, one of which is related with rules regarding the conversion of land rights.The existence of rules regarding conversion affects the rights of indigenous peoples' land, especially in Bali.This research was carried out using the approach of the statue (the statue approach) and the conceptual approach (conseptual approach). land regulation in Indonesia by establishing a LoGA which is expected to be able to provide justice and prosperity for the people of Indonesia, while the conversion rules contained in the LoGA have a positive impact but also a negative impact on the rights to land ownership of indigenous peoples, especially in Bali.